Strain and growth conditions may regulate resistance of Listeria monocytogenes biofilms to banzalkonium chloride - Bonneville, Lourenço (2020)
Listeria monocytogenes is one of the main foodborne pathogens. The formation of biofilms by L. monocytogenes contributes to its resistance to disinfectants, which represents a serious risk for food production plants. The aim of this study was to compare the e ect of sub-inhibitory concentrations of benzalkonium chloride (BAC) (1.25 or 2.5 mg/L) on biofilm production and on biofilm reduction after exposure to an inhibitory concentration of BAC (1280 mg/L) in two isogenic L. monocytogenes strains: the BAC-sensitive wild-type strain S2-1 and its BAC-resistant mutant derivative S2BAC, which presented a multidrug resistance phenotype. The biofilm-forming ability of the strains under di erent BAC concentrations was evaluated by the resazurin method using polystyrene microplates. The biofilm reduction after BAC exposure was evaluated by using stainless steel coupons (SSCs). When the resazurin method was used, S2BAC produced significantly more biofilm in the presence of a sub-inhibitory concentration of BAC compared to that in the culture medium without BAC (p < 0.05). When the SSC method was used, the presence of sub-inhibitory concentrations of BAC resulted in a higher resistance of the biofilm for S2BAC compared to that in the culture medium without BAC (p < 0.05). This was not observed with the sensitive S2-1 strain. These results suggest that biofilm behavior depends on the strain and sub-inhibitory concentrations of disinfectants and may explain the ability of certain isolates to persist in niches of food processing plants